Finland : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2005)
The staff report for the 2004 Article IV Consultation on Finland highlights economic background and policy discussions. Sustained economic growth, among the highest in the industrialized world, has been underpinned by productivity gains led by the high technology electronics sector. The medium-term fiscal prospects are shaped by the strengthening recovery and the planned tax cuts. Reducing taxation of labor has been a key element of the authorities' efforts to promote employment. The structural unemployment remains high, and Finland faces a rapidly changing global and domestic environment that calls for hard policy choices.